Reframing the narrative: an analysis of print media reporting on Bihar floods - Priya, Ritu (Frontiers in Water, 2024)
In modern ways of “knowing water,” some narratives have gained greater acceptance than others. Mass media is a major component of the complex cultural process through which such narratives are created and sustained. This article elucidates vernacular print media as the site of the construction of the dominant water meanings. Taking the case study of Hindustan, a popular Hindi newspaper from Bihar, India, this article analyzes patterns of media reporting and the resulting discourse development on water management. Newspaper articles reporting on water issues were collected for the three monsoon months of July, August, and September, 2019. The sample was taken for the monsoon season when floods and other water-related events are expected to be more heavily reported in the news. A total of 376 news items were found to report on water, in which seven major themes of reporting were identified. Second, discourse analysis was carried out on the 139 articles under the theme “monsoon floods.” These news items were analyzed according to five aspects: (i) spatial outlook; (ii) holistic approach; (iii) fact-based reporting; (iv) flood mitigation; and (v) gender-balanced reporting. Monsoon floods were the most frequently reported theme. Articles reported on both damage due to floods and the measures of flood management. It was found that news items present a spatially disconnected and parochial pattern of reporting. News stories focused more on the short-term impacts of floods than on the underlying policy problems. Fact-based reporting was limited. News items on flood mitigation were favorable to structural interventions, particularly, and embankments. The gender lens was completely absent from the study. Through this pattern of reporting, the news items created two narratives. Firstly, the news items frame floods as unwelcome disasters that are exacerbated by rainfall in the catchment areas of the upper riparian country Nepal and sluggish discharge from the Farakka Barrage. Secondly, news items also reported on the interlinking of rivers and the construction of embankments as favorable methods of flood control. This article problematizes these narratives and suggests a counter in terms of “living with floods.” Some suggestions for more nuanced and diversified reporting on the topic are discussed.